2022
DOI: 10.1093/mnras/stac2024
|View full text |Cite
|
Sign up to set email alerts
|

Abundance stratification in Type Ia supernovae – VI. The peculiar slow decliner SN 1999aa

Abstract: The abundance distribution in the ejecta of the peculiar slowly declining Type Ia supernova (SN Ia) SN 1999aa is obtained by modelling a time series of optical spectra. Similar to SN 1991T, SN 1999aa was characterised by early-time spectra dominated by Fe iii features and a weak Si ii 6355 Å line, but it exhibited a high-velocity Ca ii H&K line and morphed into a spectroscopically normal SN Ia earlier. Three explosion models are investigated, yielding comparable fits. The innermost layers are dominated by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 77 publications
0
5
0
Order By: Relevance
“…Observations of SN 1999aa (Filippenko et al 1999), which showed a premaximum spectral evolution intermediate between that of SN 1991T and normal SNe Ia (Li et al 2001b;Garavini et al 2004), supported the idea that 91T-like events are simply extreme examples of normal SNe Ia (Branch 2001;Garavini et al 2004). However, a recent abundance tomography study of SN 1999aa by Aouad et al (2022) found abundance peculiarities in the outer ejecta like those deduced for SN 1991T by Sasdelli et al (2014), concluding that a temperature increase alone cannot account for the differences between these SNe and normal events. O'Brien et al (2024) reached a similar conclusion that a combination of both abundance and ionization differences is required to explain the transition from normal to 91T-like SNe.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation

1991T-like Supernovae*

Phillips,
Ashall,
Brown
et al. 2024
ApJS
Self Cite
“…Observations of SN 1999aa (Filippenko et al 1999), which showed a premaximum spectral evolution intermediate between that of SN 1991T and normal SNe Ia (Li et al 2001b;Garavini et al 2004), supported the idea that 91T-like events are simply extreme examples of normal SNe Ia (Branch 2001;Garavini et al 2004). However, a recent abundance tomography study of SN 1999aa by Aouad et al (2022) found abundance peculiarities in the outer ejecta like those deduced for SN 1991T by Sasdelli et al (2014), concluding that a temperature increase alone cannot account for the differences between these SNe and normal events. O'Brien et al (2024) reached a similar conclusion that a combination of both abundance and ionization differences is required to explain the transition from normal to 91T-like SNe.…”
Section: Introductionmentioning
confidence: 86%
“…A pulsational-driven detonation (PDD; Khokhlov 1991b), in which an initial deflagration stalls and the inner region collapses until a detonation occurs at the border between processed and unprocessed elements, was suggested for SN 1991T by Hoeflich et al (1994). , Quimby et al (2007), and, more recently, Aouad et al (2022) have emphasized that a PDD could lead to the IMEs being confined to a relatively narrow velocity range. Nevertheless, such models predict significant amounts of unburned carbon in the outermost layers of the ejecta (Baron et al 2008), which is not observed in 91T-like SNe.…”
Section: Introductionmentioning
confidence: 99%

1991T-like Supernovae*

Phillips,
Ashall,
Brown
et al. 2024
ApJS
Self Cite
“…We place these three categories of elements into three distinct regions of the ejecta corresponding to a general structure seen in the HESMA abundance profiles as well as tomography results presented by Aouad et al (2022), Figure 18 in which IGEs resulting from complete nuclear burning are placed below a layer of IMEs resulting from incomplete burning, with UBEs placed in the outermost regions (see Figure 1). The fractional abundance of each region is parameterized by a set of functions, A UBE (v; v c , w), A IME (v; v c , w), and A IGE (v; v c , w), where the sum of the profiles at each velocity adds up to unity.…”
Section: Abundance Profilementioning
confidence: 99%
“…As such we require custom abundance profiles, derived through abundance tomography (Stehle, Mazzali & Hillebrandt 2005 ). This technique is used to develop a custom abundance profile for an assumed density profile and has been previously used to gain insights into the structure and composition of the ejected material of thermonuclear transients (Mazzali et al 2008 ;Tanaka et al 2011 ;Sasdelli et al 2014 ;Barna et al 2017 ;Aouad et al 2022 ). First, the abundances of the higher velocity material are constrained manually to match the features and shape of the earliest spectrum.…”
Section: Custom Abundance Profiles For Sn 2021rhumentioning
confidence: 99%